Reactive Magnetron Sputtering of ZrO2/Al2O3 Coatings: Alumina Content and Structure Stability - Zukerman, I.; Boxman, R.L.; Raveh, A. (Journal of Coating Science and Technology, 2015)
Ternary zirconia-alumina coatings with different compositional ratios, ranging from pure zirconia to 50% alumina content, were deposited by reactive sputtering from two targets, Zr and Al, in argon-oxygen mixtures. The coating composition was controlled by the Zr/Al target power ratio provided by two pulsed-DC power supplies. The coatings were 1 µm thick and they were deposited on floating potential substrates at a temperature of 650±3K. XRD indicated that the pure zirconia coatings possessed a monoclinic structure with a grain size of 35-40 nm. Adding alumina to the zirconia coating stabilized the cubic zirconia phase and decreased the grain size to 10-15 nm. The alumina phase in the coatings remained amorphous. The hardness of the nanocomposite structure increased from 11.6±0.5 GPa to 16.1±0.5 GPa for an alumina content of 17%. At higher alumina concentrations, the zirconia phase became amorphous and the hardness decreased to 10-11 GPa. Structure stability of the zirconia-alumina coatings was studied by measuring the coating structure and hardness after annealing at temperatures up to 1173 K. Pure zirconia (m-ZrO2) coatings had low structure stability; the hardness reached a maximum value of 18±1 GPa after annealing at a temperature of 773-873K; however, at higher annealing temperatures the hardness decreased, reaching a minimum value of 12.3±0.6 GPa after annealing at 1173K. The hardness of the nanocomposite ZrO2/Al2O3 coating with various compositions increased with annealing temperature. The hardness of a coating with an alumina content of 17% reached a high value of 19.2±0.5 GPa after annealing at 1073-1173 K. Measurements of post annealing XRD analyses indicated that the stabilization of the coating structure with c-ZrO2/a-Al2O3 phases is the reason for the higher structure stability. From the analyses of phase stability and hardness before and after annealing, we conclude that adding alumina to the zirconia phase promotes the formation of nanocomposite c-ZrO2/a-Al2O3 coatings with a markedly higher stability than single-phase m-ZrO2. Highlights: 1. ZrO2/Al2O3 nanocomposite coatings were deposited by co-sputtering from Zr and Al targets. 2. Adding alumina to the zirconia coating stabilized the cubic zirconia phase. 3. ZrO2-17% Al2O3 coatings had a grain size of 10-15 nm and a hardness of 16.1±0.5 GPa. 4. ZrO2/Al2O3 coatings maintained a high hardness after annealing at 1173K with a high value of 19 GPa for alumina content of 17%. 5. The ZrO2/Al2O3 nanocomposite coatings were crack-free after annealing at 1173K.